Literasi Pra-Nikah di Era Digital: Edukasi dan Sharing Gen- Z Tentang Kesiapan Ekonomi, Mental, Hukum Dalam Pernikahan Ideal di MAN 1 Boyolali - Nikmah, Roykhatun; Muhdi; Nur Rosidah, Zaidah; Zuhroh, Diana; Mardian, Andi; Wati, Asiah; Fitri Lestari, Arum (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
This study addresses the low level of premarital literacy among Generation Z, which has implications for economic readiness, mental preparedness, and legal understanding before marriage. The research aimed to analyze the effectiveness of an interactive premarital literacy program conducted through community service activities at MAN 1 Boyolali. The problem was the lack of structured and contextual education on premarital readiness in senior high schools. Using a educational approach with interactive lecture method, data were collected through observation, pre-test and post-test, and documentation. The participants were 50 twelfth-grade students from diverse socio-economic backgrounds. The results showed a 32% average increase in knowledge after the program, with the highest improvement in legal understanding (38%), followed by economic readiness (28%) and mental preparedness (24%). The findings confirm that integrating interactive lectures, case studies, and contextual discussions significantly enhances premarital literacy, especially in Generation Z. This study suggests incorporating premarital literacy into the school curriculum as a preventive education strategy to prepare youth for building healthy and sustainable marriages.